“AWARENESS” OF THE USE OF A SUBSEQUENT TRADEMARK AS A CONDITION OF LOSS CLAIMS FOR VIOLATION OF THE LAW TO THE EARLIER TRADEMARK DUE TO TOLERATE – POLISH LAW ON THE BACKGROUND OF THE COMPARATIVE - Trzebiatowski, Marcin (Review of European and Comparative Law, 2016)
For some time in the practice of trademark more and more often there are cases of so-called. tolerances (i.e. acquiescence) of by the proprietor of the trademark the use of similar trademark registered with the later priority. As a result of maintaining a state of tolerance for a long time there is a loss on the side of the proprietor of the earlier of the right to claim to invalidity of the later trademark, as well to prohibit its use. The main condition of such an effect is an awareness of the proprietor of the former trademark about use of the conflicting subsequent trademark. There are two basic questions relating to the above issue: 1) if such awareness is not only positive knowledge, but also the duty of knowledge, and 2) if this awareness may be the result of presumption, i.e. if it can be demonstrated by facts, for which, however, you can not deny the existence of knowledge of the proprietor of prior trademark about the presence of the later mark in a given market. The answer to both these questions should be positive, what convince the guidelines for harmonization effect in view of the international legal practice in this matter which are adopted among the members of such organization as AIPPI, including Poland.